Risk Assessment and Monitoring of Antibody Responses to Biosimilars in Chronic Inflammatory Diseases - Detrez, Iris; Gils, Ann (Current Pharmaceutical Design, 2017)
The expiry of the patent of several leading biological medicinal products has led to a surge in the development of ‘biosimilar’ products. However, in contrast to generic small-molecule medicines, biosimilars are not identical to their reference medicinal products. Full comparability in quality as well as in preclinical and clinical issues is required to register a biosimilar. The potential to induce antidrug antibodies after treatment with biological medicinal products is a safety issue that is an important consideration in the development of biosimilars and a critical aspect of regulatory filings. Regulatory authorities in the European Union require antidrug antibody responses to be evaluated and to be approached from a safety perspective: the higher the potential of immunogenicity to adversely affect a patient's health, the more diligently one should clarify the immunogenicity of the product. So far, however, no specific recommendations were given on a method for risk assessment or on the extent of the requisite antidrug antibody characterization. In this review, we will discuss the current state of knowledge on biosimilar products of infliximab, adalimumab and etanercept and present risk level–based schemes for the investigations of antidrug antibodies in non-clinical, clinical and pharmacovigilance studies.
Keywords: medicinal products